Strategi Komunikasi Garda Pangan dalam Menarik Minat Masyarakat Menjadi Relawan Pangan - Yudistira, Hilza; Cahyo Shah Adhi Pradana , Bagus; Insan Romadhan , Mohammad (Jurnal PIKMA : Publikasi Ilmu Komunikasi Media Dan Cinema, 2023)
Indonesia is ranked second in the world's food waste-producing countries. Garda Pangan is a pioneer NGO that raises the issue of food waste to the surface through volunteer movements. The development of communication technology is now making garda Pangan adapt in conveying information on their activities through Instagram. Through the diffusion of innovation how communicants can adopt new innovative ideas and how they make decisions about them. This makes many people interested in becoming mobilizers through volunteer activities. Based on the phenomenon, researchers are interested in knowing the Communication Strategy of the Food Guard in attracting people to become Food Volunteers. The research method uses a qualitative descriptive approach with observational data collection techniques and interviews. The results in this study show that the communication strategy carried out by the Garda Pangan by using content visualization in the form of images, designs, and videos and strengthened by captions to attract people's interest in becoming food volunteers is right on target.